Characterization and outcomes of urethroplasty for hypospadiasassociated urethral strictures in adults - Saavedra, Alvaro A.; Rourke, Keith F. (Canadian Urological Association Journal, 2019)
Introduction: Urethral stricture is one of the most commonly encountered complications after hypospadias repair but remains poorly described. The aim of this study is to better characterize hypospadias-associated urethral strictures (HAUS) and treatment outcomes. Methods: We conducted a retrospective analysis of 84 patients who underwent urethroplasty (UP) for HAUS from 2003–2017. Patients were characterized with regard to demographics, stricture length, location, concurrent pathology, previous surgery, type of urethroplasty, 90-day complications, and surgical success defined as the absence of stricture on cystoscopy. Univariate and survival multivariate analysis was performed. Results: Overall success was 88.1% at a mean followup of 19 months, with a 90-day complication rate of 9.5%, a 21.4% rate of urethrocutaneous fistula requiring a mean of 1.4 surgeries. Patients were categorized into one of four groups based on stricture length, location, and number of previous procedures: group 1 (66.7%) – previous failed hypospadias repair (HR) with stricture involving the entire repair; group 2 (7.1%) – “junctional stricture” at the junction of the “neourethra” and native urethra; group 3 (11.9%) – isolated bulbar stricture outside the repaired urethra; group 4 (14.3%) – urethral stricture in untreated hypospadias. Despite differing by technique (p<0.0001), stricture length (p=0.02), location (p<0.001), and number of previous repairs (p<0.001), groups did not significantly differ by success (p=0.82), complications (p=0.16), or urethrocutaneous fistula (p=0.19), whereas individual techniques did. Conclusions: UP for HAUS is often successful but patients frequently require more than one operation and have a significant risk of associated complications. Despite a broad spectrum of presentation, patients can often be categorized into one of four groups, which can help direct decision-making and obtain similar outcomes regardless of baseline differences.